Vibration and Deflection Behavior of a Coal Auger Working Mechanism. (6th January 2016) - Liu, Songyong; Ji, Huifu; Cui, Xinxia
Abstract : Because coal auger working mechanism faces problems such as excessive vibration, serious deflection, and low drilling efficiency, a new five-bit coal auger working mechanism test model was established to explore the influence factor on vibration and deflection under different conditions. Additionally, a simulation model was built to further research the effect of partial load and stabilizer arrangement, the correctness of which was proved by experiments. The results show that the vibration and deflection increase with drilling depth in thex direction, and they first increase and then gradually become stable in they direction. In addition, the vibration, deflection, and deflection force increase with the partial load. By arranging the stabilizer every five drill-rod section intervals, the vibration and deflection can be decreased by 30% and 40% in thex direction and by 14.3% and 65.7% iny direction, respectively.